E-BUDGETING TRAINING FOR OWNED BUSINESS ENTITIES VILLAGE (BUMG) IN BATOH VILAGE, BANDA ACEH - Irmawati, Irmawati; Gadeng, Tarmizi; Rusnaidi, Rusnaidi; Saputra, Dian Andra; Prety, Annisa (Universitas Muhammadiyah Aceh, 2023)
This community service is an activity that aims to improve skills in preparing calculating budgets for BUMG managers in Gampong Batoh, Lueng Bata District, Banda Aceh City. It is hoped that with this E-Budgeting Application Training, budget calculations preparation will be more effective. Village fund management is the budget most vulnerable to misuse or corruption. Village officials are the most corrupt officials in Indonesia according to ICW Lola Ester in Jakarta. The aim is to optimize expenditure according to needs and also as planning in managing finances in the village so that expenditure can be made according to the available budget, other things are aligning with strategic plans, coordinating activities from several departments, assigning responsibilities to families and evaluating performance. Keyword : Apparatus, Training, E-Budgetting, Budget Calculations